Effects of fishing rope strength on the severity of large whale entanglements. Issue 2 (1st December 2015) - Knowlton, Amy R.; Robbins, Jooke; Landry, Scott; McKenna, Henry A.; Kraus, Scott D.; Werner, Timothy B.
Abstract: Entanglement in fixed fishing gear affects whales worldwide. In the United States, deaths of North Atlantic right (Eubalaena glacialis) and humpback whales (Megaptera novaeangliae) have exceeded management limits for decades. We examined live and dead whales entangled in fishing gear along the U.S. East Coast and the Canadian Maritimes from 1994 to 2010. We recorded whale species, age, and injury severity and determined rope polymer type, breaking strength, and diameter of the fishing gear. For the 132 retrieved ropes from 70 cases, tested breaking strength range was 0.80–39.63 kN (kiloNewtons) and the mean was 11.64 kN (SD 8.29), which is 26% lower than strength at manufacture (range 2.89–53.38 kN, mean = 15.70 kN [9.89]). Median rope diameter was 9.5 mm. Right and humpback whales were found in ropes with significantly stronger breaking strengths at time of manufacture than minke whales (Balaenoptera acuturostrata) (19.30, 17.13, and 10.47 mean kN, respectively). Adult right whales were found in stronger ropes (mean 34.09 kN) than juvenile right whales (mean 15.33 kN) and than all humpback whale age classes (mean 17.37 kN). For right whales, severity of injuries increased since the mid 1980s, possibly due to changes in rope manufacturing in the mid 1990s that resulted in production of stronger ropes at the same diameter. Our results suggest that broad adoption of ropes with breaking strengths of ≤7.56 kN (≤1700 lbsf) could reduce the number of life‐threatening entanglements for large whales by at least 72%, and yet could provide sufficient strength to withstand the routine forces involved in many fishing operations. A reduction of this magnitude would achieve nearly all the mitigation legally required for U.S. stocks of North Atlantic right and humpback whales. Ropes with reduced breaking strength should be developed and tested to determine the feasibility of their use in a variety of fisheries.